Mycobacterium ulcerans disease management in Australian patients: the re‐emergence of surgery as an important treatment modality. Issue 6 (21st September 2018) - O'Brien, Daniel P.; Callan, Peter; Friedman, N. Deborah; Athan, Eugene; Hughes, Andrew; McDonald, Anthony
Abstract : With the demonstration of the effectiveness of antibiotic treatment, the management of Mycobacterium ulcerans disease has changed from a predominantly surgically to a predominantly medically treated disease. However, research among Australian patients has revealed that antibiotic treatment alone is associated with prolonged wound healing times, high rates of treatment toxicity, and the potential for significant tissue destruction associated with severe paradoxical reactions. We present the current state of M. ulcerans management in Barwon Health, Australia, where a close working relationship exists between the Plastic Surgical and Infectious Diseases units. Here treatment has evolved based on nearly 20 years of experience gained from managing more around 600 patients from a M. ulcerans epidemic on the nearby Bellarine and Mornington Peninsulas. In our experience, surgery has re‐emerged to play an important role in the treatment of M. ulcerans in improving the rate of wound healing, minimizing antibiotic associated toxicity and preventing further tissue loss associated with severe paradoxical reactions. For selected small lesions surgery without antibiotics may also be an effective treatment option, however aggressive surgical resection of lesions with wide margins through uninvolved tissue should no longer be performed. Furthermore, extensive excisional surgery that will require the use of split skin grafts and vascularized tissue flaps to repair skin defects should be avoided if possible.